Visualization and measurement of strain components in opaque and transparent samples via digital shearography - Catalan, Francesca Celine I.
Digital shearography (DS) is utilized in the investigations of strains in both diffusely scattering opaque and transparent objects. The ability of the shearographic technique to resolve strain components is shown to depend on the directions of the illuminating beam and the imaging plane. From shearography experiments using a tilted Michelson interferometry configuration, pure out-of-plane strain components of 30 microstrains was measured. In-plane strain components can be obtained using multiple illumination beam configuration. The resolution of the technique is also shown to improve with a larger amount of shear in the shearographic set-up. The location and extent of the strain are indicated by the disbribution of the shearogram fringe pattern. The number of fringes is shown to increase with greater amount of strain. In this study, DS is applied in the investigations of deforming Plexiglas sample which is a transparent material. To generate the speckles when a coherent beam illuminates the Plexiglas, the surface was nominally scratched. Speckle patterns corresponding to deformed and undeformed states are subtracted to obtain the shearographic fringes. From fringe analysis, the DS set-up can resolve out-of-plane strain components in the order of 60 microstrains. For a more complete analysis of the deformation, Fourier digital holography was utilized to obtain the three-dimensional displacement distribution. Qualitative analysis of the derivative of the deformation generated through holography indicates good correlation with the shearographic results.